2021
DOI: 10.1016/j.prdoa.2021.100104
|View full text |Cite
|
Sign up to set email alerts
|

A bidirectional relationship between anxiety, depression and gastrointestinal symptoms in Parkinson’s disease

Abstract: Highlights Gastrointestinal (GI) and mood symptoms are common in Parkinson’s disease. Depression and anxiety are bidirectional risk factors for GI distress. Association between GI and mood symptoms may reflect disrupted Gut-Brain axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Anxiety disorders are the foremost prevalent psychiatric disorders among the general population [ 23 ]. Ample scientific reports indicated that the clinical characteristics of anxiety and GI dysfunctions coexist to a more significant extent [ 24 , 25 ]. To note, the pestilent symptoms of both anxiety and GI disorders have been mutually known to predispose and exacerbate the pathogenic signatures between them but the definitely combined etiology of these diseases remains obscure due to their co-morbid nature [ 24 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety disorders are the foremost prevalent psychiatric disorders among the general population [ 23 ]. Ample scientific reports indicated that the clinical characteristics of anxiety and GI dysfunctions coexist to a more significant extent [ 24 , 25 ]. To note, the pestilent symptoms of both anxiety and GI disorders have been mutually known to predispose and exacerbate the pathogenic signatures between them but the definitely combined etiology of these diseases remains obscure due to their co-morbid nature [ 24 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from 10 national or international sites from were utilized in the current sample (see https://www.ppmi-info.org/about-ppmi/ppmi-clinical-sites for a complete list of sites). The sample has 100% (Jones, Dominguez, et al, 2021; Jones, Timblin, et al, 2021; Jones, Uribe, et al, 2021), 88% (Jones, Burroughs, et al, 2020; Jones, Rahmani, et al, 2020), and 64% (Jones et al, 2019) overlap with our past work. For additional details, please see Marek et al (2011) and https://www.ppmi-info.org/.…”
Section: Methodsmentioning
confidence: 98%
“…Gut microbiotic changes that play a crucial role in the bidirectional communication between the gut and the brain (Klann et al 2022 ) with a close link between multiple movement disorders and gastrointestinal dysfunction (Talman and Pfeiffer 2022 ), suggest that the gut microbes may shape neuronal development, modulate neurotransmission and affect behavior, have been associated with the pathomechanism of DPD (Dogra et al 2022 ; Mendonça et al 2020 ; Moustafa et al 2021 ; Socala et al 2021 ) (Felice et al 2016 ; Jones et al 2021 ; Tan et al 2022 ; Xie et al 2022 ). There is increasing evidence for the highly complex relationship between the gut and the brain in PD, including the potential role of the vagus nerve, αSyn deposition in the enteric nervous system, related to intestinal permeability, autonomic dysfunction, inflammation, neural immune system and the gut microbiome (Nowak et al 2022 ; Tan et al 2022 ; Tansey et al 2022 ; Warnecke et al 2022 ).…”
Section: The Gut-brain Axismentioning
confidence: 99%